Maritime Dispute Settlement Law towards Sustainable Fishery Governance: The Politics over Marine Spaces vs. Audacity of Applicable International Law - M Jahanzeb Butt; Khadija Zulfiqar; Yen-Chiang Chang; Ali M. A. Iqtaish (Fishes, 2022)
The present article discusses and analyses the role and contribution of International Maritime Dispute Settlement Bodies in sustainable fishery governance. From a maritime dispute settlement perspective, the discussion on preserving marine biodiversity, including fisheries and ecosystems, is unprecedented. However, dispute settlement impacts on marine biodiversity require serious attention from the viewpoint of effective implementation of the United Nations Fish Stocks Agreement, International Environmental Law, and United Nations Convention on Law of the Sea. ‘Applicable law’ as primary contention, which could be utilised to preserve marine biodiversity, is preferably employed for ‘ship release’ and ‘delimitation’ issues under dispute settlement mechanisms. Perhaps, the political and legal obstacles in interpreting the ‘law of the sea’ are one area of critique, and the optional dispute settlement mechanism is another. All these significant issues are discussed to develop a rational approach utilising ‘applicable law’ to preserve marine biodiversity and develop sustainable fishery governance. The result will certainly help build a better understanding of the ‘applicable law’ jurisdiction that may be utilised to ensure the sustainability of marine biodiversity.